EVALUATING THE EFFECTIVENESS OF VILLAGE FUND POLICY IN STRENGTHENING LOCAL ECONOMIC RESILIENCE: EVIDENCE FROM SLEMAN REGENCY, INDONESIA - Saptayuda, Agusfyan (Alqaprint Jatinangor, 2024)
This study critically evaluates the effectiveness of Indonesia's Village Fund policy in enhancing local economic resilience, with a specific focus on Sleman Regency. Recognizing the Village Fund as a strategic fiscal tool to empower rural communities, the research adopts a literature review methodology to synthesize findings from existing scholarly and policy-based sources. The study explores the policy’s design, implementation mechanisms, and its alignment with community-driven economic development. Key themes include governance quality, participatory planning, fund utilization efficiency, and socio-economic outcomes. A thematic analysis reveals that while the policy shows potential in improving rural livelihoods, challenges such as bureaucratic rigidity and limited capacity at the village level persist. The evidence also suggests significant regional disparities in policy impact, highlighting the need for context-sensitive governance strategies. By integrating perspectives from empirical case studies and theoretical frameworks, this research contributes to a deeper understanding of policy effectiveness in rural economic strengthening. The paper also provides critical insights for policymakers aiming to refine the Village Fund framework. Overall, the findings underscore the importance of adaptive, inclusive, and accountable approaches to village-level fiscal decentralization.